Layer-by-layer inkjet printing SPS:PEDOT NP/RGO composite film for flexible humidity sensors. Issue 114 (1st December 2016) - Yuan, Yan; Peng, Bo; Chi, Hang; Li, Cong; Liu, Ren; Liu, Xiaoya
Abstract : We report the preparation of poly(3, 4-ethylenedioxythiophene) (PEDOT) nanoparticles (NPs) and graphene oxide (GO) ink-based layer-by-layer inkjet printing humidity sensors. Abstract : We report the preparation of poly(3, 4-ethylenedioxythiophene) (PEDOT) nanoparticles (NPs) and graphene oxide (GO) ink-based layer-by-layer inkjet printing humidity sensors. Sulfonate polystyrene:PEDOT NPs (SPS:PEDOT NPs) were prepared with hard template SPS NPs and GO was synthesized through a modified Hummers' method. Next, the SPS:PEDOT NP/GO multilayer films were printed layer by layer, with one layer of GO followed by one layer of SPS:PEDOT NP ink on the flexible poly-ethylene terephthalate (PET) substrate by using a home inkjet printer. The morphology and structure of the SPS:PEDOT NPs and GO were characterized through TEM and Raman spectroscopy and those of the film were investigated through optical microscopy. SPS:PEDOT NP-reduced GO (SPS:PEDOT NP/RGO) composite sensors were obtained after thermal annealing. To assess their humidity sensing properties, the sensors were exposed to a wide range of relative humidities (RH 0–98%) at room temperature. The SPS:PEDOT NP/RGO PET-based sensor exhibited superior humidity sensing properties in a wide response range (0.13–68.46%), short response and recovery time (39 and 57 s, respectively), and excellent repeatability and flexibility. The resistance of sensors was almost invariable even after folding 200 times. Overall, the SPS:PEDOT NP/RGO PET-based sensors can be used as humidity sensors.